Juridical Review of The Legal Responsibility of Perpetrators of Corruption Offences in Indonesia - Al' Ain Danis; Syaiful Asmi Hasibuan (International Journal of Law and Society, 2024)
In the recent reform era, there has been no effective effort to eradicate corruption. This is particularly ironic, given that the goal of reform is to eradicate corruption, collusion and nepotism (KKN). It also shows that more democratic governments are not serious about eradicating corruption. The crime of corruption in Indonesia has been increasing year by year. Corruption has become an extraordinary crime. Thus, efforts to eradicate it can no longer be done in an ordinary way, but are required in an extraordinary way. Corruption can pose a danger to the life of mankind, because it has penetrated the world of education, health, provision of food for the people, religion, and other social service functions. The difficulty of overcoming corruption can be seen from the number of acquittals of defendants in corruption cases or the lack of punishment borne by defendants who are not proportional to what they have done. This is very detrimental to the State and hampers the development of the nation. In this case, corruption cases are also difficult to disclose because the perpetrators use sophisticated equipment and are usually committed by more than one person in a covert and organised situation. Overcoming corruption requires measures such as improving the system, including improving the applicable laws and regulations, improving the way government works, strictly separating state ownership and private ownership, enforcing professional ethics and institutional discipline, applying the principles of good governance and optimising the use of technology and improving human beings, including improving human morals as believers, improving legal awareness, increasing legal awareness, electing leaders who are clean, honest and anti-corruption.